Cell interactome in sarcopenia during aging. Issue 2 (17th February 2022) - González‐Blanco, Laura; Bermúdez, Manuel; Bermejo‐Millo, Juan C.; Gutiérrez‐Rodríguez, José; Solano, Juan J.; Antuña, Eduardo; Menéndez‐Valle, Iván; Caballero, Beatriz; Vega‐Naredo, Ignacio; Potes, Yaiza; Coto‐Montes, Ana
Abstract: Background: The diversity between the muscle cellular interactome of dependent and independent elderly people is based on the interrelationships established between different cellular mechanisms, and alteration of this balance modulates cellular activity in muscle tissue with important functional implications. Methods: Thirty patients (85 ± 8 years old, 23% female) scheduled to undergo hip fracture surgery participated in this study. During the surgical procedures, skeletal muscle tissue was obtained from the Vastus lateralis . Two groups of participants were studied based on their Barthel index: 15 functional‐independent individuals (100‐90) and 15 severely functional‐dependent individuals (40‐0). The expression of proteins from the most important cellular mechanisms was studied by western blot. Results: Compared with independent elderly patients, dependent elderly showed an abrupt decrease in the capacity of protein synthesis; this decrease was only partially compensated for at the response to unfolded or misfolded proteins (UPR) level due to the increase in IRE1 ( P < 0.001) and ATF6 ( P < 0.05), which block autophagy, an essential mechanism for cell survival, by decreasing the expression of Beclin‐1, LC3, and p62 ( P < 0.001) and the antioxidant response. This lead to increased oxidative damage to lipids ( P < 0.001) and that damage was directly associated with the mitochondrial impairment induced by the significant decreases in the I, III, IV, and V mitochondrial complexes ( P < 0.01), which drastically reduced the energy capacity of the cell. The essential cellular mechanisms were generally impaired and the triggering of apoptosis was induced, as shown by the significantly elevated levels of most proapoptotic proteins ( P < 0.05) and caspase‐3/7 ( P < 0.001) in dependents. The death of highly damaged cells is not detrimental to organs as long as the regenerative capacity remains unaltered, but in the dependent patients, this ability was also significantly altered, which was revealed by the reduction in the myogenic regulatory factors and satellite cell marker ( P < 0.001), and the increase in myostatin ( P < 0.01). Due to the severely disturbed cell interactome, the muscle contractile capacity showed significant damage. Conclusions: Functionally dependent patients exhibited severe alterations in their cellular interactome at the muscle level. Cell apoptosis was caused by a decrease in successful protein synthesis, to which the cellular control systems did not respond adequately; autophagy was simultaneously blocked, the mitochondrion malfunctioned, and as the essential recovery mechanisms failed, these cells could not be replaced, resulting in the muscle being condemned to a loss of mass and functionality.